2019
DOI: 10.1016/j.addbeh.2018.07.021
|View full text |Cite|
|
Sign up to set email alerts
|

Correct knowledge of medical cannabis legal status in one's own state: Differences between adolescents and adults in the United States, 2004–2013

Abstract: Lower MCL knowledge among adolescents than adults was in accordance with MCL effects on cannabis use previously observed among adults only. Studies should assess whether MCL knowledge is a consequence or predictor of individual-level cannabis use across age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
2
4
0
1
Order By: Relevance
“…Public knowledge of legislation adds further complexity. A US study found that adolescents had lower knowledge of medical cannabis laws (MCL) than adults, adjusting for state‐level cannabis use prevalence, MCL enactment, and open dispensaries [7]. Accumulating evidence indicates that cannabis use is changing at different rates than policy and attitude changes [8], suggesting that drivers of each should be considered as separate time‐varying processes.…”
Section: Introductionmentioning
confidence: 99%
“…Public knowledge of legislation adds further complexity. A US study found that adolescents had lower knowledge of medical cannabis laws (MCL) than adults, adjusting for state‐level cannabis use prevalence, MCL enactment, and open dispensaries [7]. Accumulating evidence indicates that cannabis use is changing at different rates than policy and attitude changes [8], suggesting that drivers of each should be considered as separate time‐varying processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although having a low THC oil card allows the patient to be in possession of the oil and protects them from arrest for THC possession, the law does not provide any details related to accessing low THC oil. 8 As of July 2018, there were 648 physicians and 5,425 patients listed on Georgia's low THC oil registry. 9 Given the lack of consistent access to cannabis products, conflicting state and federal cannabis laws, 3 and differing opinions among health care professionals regarding the use of cannabis, 10 we conducted a survey to assess patients who have a low THC oil card in an ambulatory palliative care clinic in the State of Georgia to determine their perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Hasin et al (2017) con datos procedentes de encuestas realizadas en ese mismo país de 1991 a 2013 (estudios NLAES y NESARC) señalan que el cannabis medicinal legal aumenta la prevalencia del consumo ilegal y de TUC. Así, Mauro et al (2019) en una encuesta nacional sobre consumo de drogas en EE.UU. señala un incremento en ambos sexos en el consumo en los mayores de 26 años.…”
Section: Cambios En El Consumo En Adultosunclassified